2020
DOI: 10.1039/d0ma00522c
|View full text |Cite
|
Sign up to set email alerts
|

Binary treatment of PEDOT:PSS films with nitric acid and imidazolium-based ionic liquids to improve the thermoelectric properties

Abstract: Abstract. Poly(3,4-ethylenedioxythiophene):poly-(styrenesulfonate) (PEDOT:PSS) is one of most prominent organic conductive polymer-based thermoelectric (TE) materials. Numerous combinations of doping and dedoping processes have been demonstrated to optimize the doping level of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…40 Later Kee et al reported that ionic liquids consisting of EMIM DCA or EMIM DCl can manipulate the doping level and nanostructure of PEDOT:PSS through ion exchange, which leads to a remarkable increase in the conductivity and Seebeck coefficient (up to 538 S cm À1 and 35 mV K À1 , respectively). 41 Similar contributions have been realized for PEDOT:PSS lms constructed by ionic liquid coatings based on BMIM or EMIM cations with various anions; [42][43][44][45][46][47][48][49][50][51][52][53] and their thermoelectric performances are summarized in Table S1. † The addition of or treatment with these ionic liquids in previous studies indicates the direction for manipulating the thermoelectric performance.…”
Section: Introductionmentioning
confidence: 64%
“…40 Later Kee et al reported that ionic liquids consisting of EMIM DCA or EMIM DCl can manipulate the doping level and nanostructure of PEDOT:PSS through ion exchange, which leads to a remarkable increase in the conductivity and Seebeck coefficient (up to 538 S cm À1 and 35 mV K À1 , respectively). 41 Similar contributions have been realized for PEDOT:PSS lms constructed by ionic liquid coatings based on BMIM or EMIM cations with various anions; [42][43][44][45][46][47][48][49][50][51][52][53] and their thermoelectric performances are summarized in Table S1. † The addition of or treatment with these ionic liquids in previous studies indicates the direction for manipulating the thermoelectric performance.…”
Section: Introductionmentioning
confidence: 64%
“…A high-performance DES should induce not only an efficient ion exchange with PEDOT:PSS to increase mobility but also a uniform high-level p-doping of PEDOT that increases its intrinsic conductivity. 34…”
Section: Resultsmentioning
confidence: 99%
“…[138] With this technique, S of the films increased from 28 to 49.3 µV K −1 while σ reduced from 1647 to 783 S cm −1 due to the decrease of its and with a ZT value of 0.12 at 300 K were obtained for the films. [139] In another study, 1D-PEDOT:PSS fibers were developed via wet-spinning process followed by treatment with sulfuric acid (H 2 SO 4 ), as a result, high σ and S values of 4029.5 S cm −1 and 19.2 µV K −1 were obtained, respectively. [140] As aforementioned, doping PEDOT:PSS with solvents can greatly enhance its σ, meanwhile dedoping can significantly increase S while substantially lowering σ.…”
Section: Seebeck Coefficient [µV Kmentioning
confidence: 99%
“…A significant σ value of 1260 S cm −1 , enhanced S value from ≈16 to 34.8 µV K −1 and with a ZT value of 0.12 at 300 K were obtained for the films. [ 139 ] In another study, 1D‐PEDOT:PSS fibers were developed via wet‐spinning process followed by treatment with sulfuric acid (H 2 SO 4 ), as a result, high σ and S values of 4029.5 S cm −1 and 19.2 µV K −1 were obtained, respectively. [ 140 ]…”
Section: Promising Thermoelectric Materialsmentioning
confidence: 99%